CURRENT ISSUES OF PHARMACEUTICAL WASTE MANAGEMENT IN THE SYSTEM OF ENVIRONMENTAL AND SANITARY SAFETY (Marketing Journal, 2025)
This article examines the danger of pharmaceutical waste, which consists in the fact that it: constantly enters the environment and exhibits stability, negatively affects natural components even in small concentrations (especially aquatic fauna), in case o f contact with other pharmaceutical substances, potentially creates a synergistic and cumulative effect. The main source of environmental pollution with pharmaceutical waste is wastewater discharges, landfills, large farms, from where undigested pharmaceut ical substances enter surface and ground water. The article also provides 370 regulatory legal acts in the field of recycling and processing of waste from industrial enterprises and the chemical industry.
Keywords: medicines; environmental pollution; pharmaceutical pollutants; drinking water; pharmaceuticals